ARTICLE RETRACTED DUE TO PLAGIARISM BY THE AUTHOR El efecto de la carrera aeróbica en el pensamiento y la resistencia de los niños (The effect of aerobic running on children’s thinking and endurance): ARTICLE RETRACTED DUE TO PLAGIARISM BY THE AUTHOR - Polevoy, Georgiy (Retos, 2024)
El objetivo es evaluar el impacto de la carrera prolongada en los indicadores de resistencia y pensamiento de niños de 9 a 10 años en las clases de educación física en la escuela. Métodos: el experimento pedagógico se llevó a cabo durante 4 meses sobre la base de la escuela secundaria de educación general 60 (Kirov, Rusia), participaron 120 escolares de tercer grado. se impartieron 34 lecciones de educación física en cada clase. Los escolares del grupo de control participaron en un programa estándar de educación física para escolares más pequeños. Los niños del grupo experimental también trabajaron en el marco del programa habitual, pero durante cada lección realizaron una carrera larga de 6 minutos. La resistencia general se evaluó mediante la prueba K Cooper (6 minutos), el pensamiento de los estudiantes se evaluó mediante la prueba de "Analogías simples". Ambas pruebas se realizaron antes y después del experimento pedagógico. Resultados-antes del inicio del estudio, no hubo diferencias significativas entre clases en ambas pruebas (p>0,05). Tras la finalización del estudio, el rendimiento de los niños del grupo control mejoró en la prueba de resistencia en un 6,8% y un 7,2% (p>0,05), y en el grupo experimental mejoró en un 24,9% y un 18,9% (p<0,05). En la prueba de pensamiento, los indicadores del grupo control aumentaron un 7,3% y un 8,4% (p > 0,05), y en el grupo experimental un 24,8% y un 23,5% (p < 0,05). Conclusión: se puede introducir la carrera larga en el programa de educación física en la escuela para mejorar el rendimiento de resistencia y el pensamiento de los escolares de 9 a 10 años. Palabras Clave: Salud, Cultura física, Habilidades aeróbicas, Cualidades físicas, Psicodiagnóstico, Currículo escolar. Abstract. The aim is to assess the impact of prolonged running on the endurance and thinking indicators of children aged 9-10 years in physical education classes at school. Methods – the pedagogical experiment was conducted for 4 months on the basis of the secondary general educational school 60 (Kirov, Russia), 120 schoolchildren from the third grades took part in it. 34 physical education lessons were held in each class. Schoolchildren from the control group were engaged in a standard physical education program for younger schoolchildren. The children from the experimental group also worked within the framework of the usual program, but during each lesson they performed a long run of 6 minutes. Overall endurance was assessed using the K Cooper (6 minutes) test, the students’ thinking was evaluated by the "Simple Analogies" test. Both tests were performed before and after the pedagogical experiment. Results – before the start of the study, there were no significant differences between classes in both tests (p>0.05). After the end of the study, the performance of children in the control group improved in the endurance test by 6.8% and 7.2% (p>0.05), and in the experimental group improved by 24.9% and 18.9% (p<0.05). In the thinking test, the indicators of the control group increased by 7.3% and 8.4% (p>0.05), and in the experimental group by 24.8% and 23.5% (p<0.05). Conclusion – long running can be introduced into the physical education program at school to improve endurance performance and thinking of schoolchildren 9-10 years old. Keywords: Health, Physical culture, Aerobic abilities, Physical qualities, Psychodiagnostics, School curriculum.